Differential impacts of physical activity volume and intensity on blood lead levels in children and adolescents: a cross-sectional study - Shengrong Ouyang; Yan Yin; Yuanyuan Li; Jianxin Wu; Zhuo Liu (BMC Public Health)
Abstract Background Previous studies on physical activity (PA) and blood lead levels (BLLs) have relied on self-reported data, conflating PA volume and intensity. This study aimed to disentangle their independent effects and test the hypothesis that higher PA volume increases BLLs via environmental lead exposure, while higher PA intensity reduces BLLs through enhanced excretion. Methods We used data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES) to quantify PA in 3,249 U.S. children and adolescents (aged 3–19 years) using two metrics based on monitor-independent movement summary units (MIMS): average daily MIMS for volume and peak 60-minute MIMS for intensity. BLLs were natural log-transformed (ln-BLL) for analysis. Weighted multivariable linear regression, general additive models, mediation analysis, and Bayesian kernel machine regression (BKMR) were employed to explore associations. Results PA volume showed a significant positive association with ln-BLL (β = 0.025, p < 0.001), with a threshold effect at 19,700 MIMS. In contrast, PA intensity exhibited a non-significant negative correlation with BLL (β = -0.027, p = 0.156). Mediation analysis indicated that outdoor time explained 32.8% of the PA volume–BLL association. BKMR revealed cumulative effects of co-exposures on BLL trends. Sex-stratified analyses showed that males had higher BLLs at similar PA volume levels, while females experienced greater reductions in BLLs with increased PA intensity. Conclusion Our findings support a dual-pathway model: greater PA volume may elevate BLL—particularly in males—while higher intensity may reduce BLL—especially in females. These results underscore the need for PA guidelines that balance volume and intensity, optimize sweat-promoting exercise in low-lead environments, and inform interventions to safeguard the health of children and adolescents against lead exposure.